2008
DOI: 10.1186/1471-2164-9-572
|View full text |Cite
|
Sign up to set email alerts
|

A novel custom high density-comparative genomic hybridization array detects common rearrangements as well as deep intronic mutations in dystrophinopathies

Abstract: Background: The commonest pathogenic DMD changes are intragenic deletions/duplications which make up to 78% of all cases and point mutations (roughly 20%) detectable through direct sequencing. The remaining mutations (about 2%) are thought to be pure intronic rearrangements/ mutations or 5'-3' UTR changes. In order to screen the huge DMD gene for all types of copy number variation mutations we designed a novel custom high density comparative genomic hybridisation array which contains the full genomic region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 26 publications
(23 reference statements)
2
67
0
Order By: Relevance
“…In conclusion, this large survey of 50 patients confirmed the previous observations [10][11][12][13] that array-CGH is a reliable and effective tool in detecting simple and complex DMD rearrangements. This approach offers some advantages over exon-based detection methods as it can identify pure intronic pathogenic events and it allows precise delineation of rearrangements, some of which may affect the splicing process.…”
Section: Discussionsupporting
confidence: 87%
“…In conclusion, this large survey of 50 patients confirmed the previous observations [10][11][12][13] that array-CGH is a reliable and effective tool in detecting simple and complex DMD rearrangements. This approach offers some advantages over exon-based detection methods as it can identify pure intronic pathogenic events and it allows precise delineation of rearrangements, some of which may affect the splicing process.…”
Section: Discussionsupporting
confidence: 87%
“…Intronic duplications potentially disrupting the splicing machinery have also been reported to be pathogenic. 27 In our study, we found de novo duplications in one s-JIA patient, which involve many important genes for the regulation of the immune system. Other patients without any pathological CNVs in this study may have point mutations of a gene(s) mapped to the duplications, which may lead to upregulated gene expression causative for s-JIA as previously described in a different disease.…”
Section: Discussionmentioning
confidence: 54%
“…[7][8][9]). This method uses thousands of oligonucleotides to interrogate copy number across the entire 2.2 MB genomic region of the DMD gene including all exons and introns, and thereby maps rearrangement breakpoints to relatively narrow intervals depending on the spacing of the oligonucleotides at the breakpoints.…”
Section: Testing For Deletions and Duplicationsmentioning
confidence: 99%
“…If a duplication of a single or multiple exons is identified it is important to test all exons for the possibility of additional exons being duplicated, since a number of apparently non-continuous duplications have been reported [9,10].…”
Section: Testing For Deletions and Duplicationsmentioning
confidence: 99%